COVID-19 Antibody Testing of Patients Admitted to the ICU by A Novel, Point-of-Care Assay, and the Relationship to Survival - S, Casswell; AK, Eriksson; L, Moberg; M, Lipcsey; M, Hultstrom; M, Frithiof; P, Venge (Archives of Clinical and Biomedical Research, 2021)
Diagnosing persons infected by COVID-19 is key to the control of the pandemic. It has, however, become increasingly important to identify those who have had the infection by measurement of circulating antibodies against Sars-COV-2 of the IgM and IgG type. In this report we show the development of a rapid and sensitive point-of-care assay for the measurement of IgG antibodies against the two spike proteins, S1 and S2, of the Sars-COV-2 virus. Methods: The AgPlus electrochemical technology was applied and the S1 and S2 proteins were biotinylated and immobilized onto streptavidin coated magnetic particles as the capture component of the assay. The IgG antibodies bound to the particles were detected by anti-human IgG and the signal expressed as nC (nano Coulomb). Assay time was <10 min. Results: Plasma (n=211) from 117 SARS-Cov-2 PCR positive patients and from 78 persons with samples taken before the COVID-19 pandemic were analysed. The sensitivity and specificity of the assay were 91.9% and 100%, respectively. The assay was highly correlated to a predicate and FDA-approved IgG antibody ELISA (r=0.81). The IgG response was significantly lower in patients who died during their ICU stay. Conclusions: A poor IgG response after a COVID-19 infection is a serious risk factor as to death. A sensitive, rapid and accurate IgG antibody POC assay should be useful in the daily management and evaluation of COVID-19 infected patients.